STUDI KRITIK TERHADAP PEMIKIRAN KH. AHMAD DAHLAN DALAM PENENTUAN ARAH KIBLAT DAN AWAL BULAN QAMARIYAH - Imroatul Munfaridah (At-Taqaddum, 2011)
This study seeks to reveal and explain the thinking of KH. Ahmad Dahlan about the direction of Qibla, the beginning of the month Qamariyah and the extent of the influence of KH. Ahmad Dahlan in Muhammadiyah related to astronomy.This study uses the approach of astronomy (falaq) or astronomy that are characteristic of astronomy research is supported by interviews and documentation to obtain representative data. These approaches can be found the results, namely: First, KH. Ahmad Dahlan able to create a theory to determine the direction of  Qibla ie using a globe, which was not yet so advanced technology, with a globe that KH. Ahmad Dahlan diligence that the direction of the Qibla of Yogyakarta city in general and in particular the Great Mosque is 240, when compared with the contemporary direction of qibla calculation software is less oblique to the right  1  15 '0 "(one degrees fifteen minutes zero seconds) of a real Kiblat, while from calculation formula triangle ball of qibla direction is less oblique to the right  0  42 '21.88".  Second, for the first time KH. Ahmad Dahlan determine the beginning of the month taqribi Qamariyah is essential to follow his teacher K. Dahlan Termas with the book of al-Ihwan Tazkir that tend to geocentric. But after Djalaluddin studied with Sheikh Taher, KH. Ahmad Dahlan move to the intrinsic reference Tahkiki using Matla 'al-Sa'id who tend to be heliocentric. Third, KH. Ahmad Dahlan with Muhammadiyah has a linkage between the two, because the ideas KH. Ahmad Dahlan until now been adopted and used by Muhammadiyah in issues related to the astronomy.